Analisis Tanggung Jawab dan Kedudukan Hukum Perseroan Terbatas Dalam UU Perseroan Terbatas dan UU Cipta Kerja - Salomo; Swanis Swanis; Aldy Mubarǫ; Abdul Muhajir (Pusat Riset dan Inovasi Nasional, 2024)
Limited Liability Companies (PT) are legal entities that have an important role in the modern economy. This research aims to analyze the responsibilities and legal position of PT in the Limited Liability Company Law. Through a descriptive-analytical approach. First, this research reviews the regulations governing PT organizational responsibilities, which include the separation between ownership, management and legal responsibilities. Second, this research discusses the legal position of limited liability companies The research results show that PT plays a key role and responsibility in increasing economic growth and providing legal protection for stakeholders. Careful and comprehensive regulations are needed to ensure that HEIs operate ethically, transparently and in accordance with sustainability principles. The implication of this research is the importance of a deep understanding of PT regulations for legal practitioners, entrepreneurs and other stakeholders to create a stable and sustainable economic environment.